2015
DOI: 10.1038/leu.2015.91
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and biological implications of ancestral and non-ancestral IDH1 and IDH2 mutations in myeloid neoplasms

Abstract: Mutations in isocitrate dehydrogenase 1/2 (IDH1/2MT) are drivers of a variety of myeloid neoplasms. As they yield the same oncometabolite, D-2-hydroxyglutarate, they are often treated as equivalent, and pooled. We studied the validity of this approach and found IDH1/2 mutations in 179 of 2119 myeloid neoplasms (8%). Cross-sectionally, the frequencies of these mutations increased from lower- to higher-risk disease, thus suggesting a role in clinical progression. Variant allelic frequencies indicated that IDH1MT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 34 publications
2
73
1
3
Order By: Relevance
“…The combined effects of all these changes lead to a block in myeloid differentiation and accumulation of DNA damage in HSC/myeloid progenitors that is oncogenic unlike TET2 mutations, IDH1/2 mutations are quite rare in clonal hematopoiesis of indeterminate potential. IDH1/2 mutation frequency is higher in de novo AML than in chronic myeloid neoplasms [40], whereas the greatest incidence (50 %) of TET2 mutations occurs in CMML, in agreement with the myelomonocytic proliferation in TET2 KO mice. Thus, IDH1/2 mutations appear to have higher oncogenic potential than TET2 mutations and are associated with more aggressive diseases [1,2].…”
Section: Tet2 and Idh1/2 Mutations In Hematological Disorderssupporting
confidence: 53%
“…The combined effects of all these changes lead to a block in myeloid differentiation and accumulation of DNA damage in HSC/myeloid progenitors that is oncogenic unlike TET2 mutations, IDH1/2 mutations are quite rare in clonal hematopoiesis of indeterminate potential. IDH1/2 mutation frequency is higher in de novo AML than in chronic myeloid neoplasms [40], whereas the greatest incidence (50 %) of TET2 mutations occurs in CMML, in agreement with the myelomonocytic proliferation in TET2 KO mice. Thus, IDH1/2 mutations appear to have higher oncogenic potential than TET2 mutations and are associated with more aggressive diseases [1,2].…”
Section: Tet2 and Idh1/2 Mutations In Hematological Disorderssupporting
confidence: 53%
“…MT confer a worse prognosis in AML patients (45). One difference between AML and glioma is that IR is typically not used to treat AML, whereas it is routinely used as a treatment modality for glioma.…”
Section: Idhmentioning
confidence: 99%
“…6,[8][9][10] Although both mutations are characterized by neomorphic enzymatic activity, myeloid malignancies with R140 and R172 IDH2 mutations are distinct with respect to clinical outcome, comutational profile, and molecular classification. [11][12][13] In preclinical studies, enasidenib (AG-221/CC-90007), a small-molecule inhibitor of mIDH2, reduced serum 2-HG, DNA hypermethylation, and repressive histone marks and promoted hematopoietic differentiation in R140 and R172 mIDH2 models. [14][15][16][17] In a phase 1/2 clinical trial, enasidenib demonstrated clinical activity in patients with both R140 and R172 mIDH2 relapsed/refractory AML (rrAML) with an overall response rate (ORR) of 40.3%.…”
Section: Introductionmentioning
confidence: 99%